2016
DOI: 10.1016/j.psyneuen.2015.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a unique and common genetic etiology between the CAR and the remaining part of the diurnal cycle: A study of 14 year-old twins

Abstract: Introduction: By and large, studies have reported moderate contributions of genetic factors to cortisol secreted in the early morning and even smaller estimates later in the day. In contrast, the cortisol awakening response (CAR) has shown much stronger heritability estimates, which prompted the hypothesis that the etiology of cortisol secretion may vary according to the time of day. A direct test of this possibility has, however, not yet been performed. Objective: To describe the specific and common etiology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 49 publications
(74 reference statements)
1
15
0
Order By: Relevance
“…While stressful environmental factors play a major role in HPA axis activation, twin studies have indicated that genetic factors have a substantial impact on the secretion of cortisol, especially morning cortisol. Predominantly moderate heritability estimates have been reported in adults (as reviewed in refs 25 27 ) and adolescents 25 , 27 , 28 . The observed heritability of HPA axis regulation suggests a contribution of genetically determined biological mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…While stressful environmental factors play a major role in HPA axis activation, twin studies have indicated that genetic factors have a substantial impact on the secretion of cortisol, especially morning cortisol. Predominantly moderate heritability estimates have been reported in adults (as reviewed in refs 25 27 ) and adolescents 25 , 27 , 28 . The observed heritability of HPA axis regulation suggests a contribution of genetically determined biological mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to effects of caregiving and the psychosocial environment, physiological attunement could also reflect shared genes. Approximately 30% of the variance in waking cortisol is attributed to genetic influences (Bartels, Geus, Kirschbaum, Sluyter, & Boomsma, ; Ouellet‐Morin et al, , ; Van Hulle, Shirtcliff, Lemery‐Chalfant, & Goldsmith, ) while little to 0% of afternoon or evening cortisol is attributable to genetics (Bartels et al, ; Schreiber et al, ; Van Hulle et al, ). Further about 30% of cortisol slope is explained by genetics (Ouellet‐Morin et al, ; Van Hulle et al, ), potentially due to the genetic influence on waking levels.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 30% of the variance in waking cortisol is attributed to genetic influences (Bartels, Geus, Kirschbaum, Sluyter, & Boomsma, ; Ouellet‐Morin et al, , ; Van Hulle, Shirtcliff, Lemery‐Chalfant, & Goldsmith, ) while little to 0% of afternoon or evening cortisol is attributable to genetics (Bartels et al, ; Schreiber et al, ; Van Hulle et al, ). Further about 30% of cortisol slope is explained by genetics (Ouellet‐Morin et al, ; Van Hulle et al, ), potentially due to the genetic influence on waking levels. However, most studies have been with older children (Bartels et al, ; Ouellet‐Morin et al, ; Schreiber et al, ; Van Hulle et al, ), with only one infant study that involved one waking sample on a single day (Ouellet‐Morin et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of previous studies investigating genetic variation of cortisol secretion have examined static cortisol levels rather than changes in cortisol over time (Rietschel et al, 2017;Tucker-Drob et al, 2017). The few studies that have examined the contribution of genetic variation to cortisol reactions or diurnal change have reported sizable heritability estimates (Federenko, Nagamine, Hellhammer, Wadhwa, & Wüst, 2004;Ouellet-Morin et al, 2016;Van Hulle, Shirtcliff, Lemery-Chalfant, & Goldsmith, 2012). It remains unknown whether heritable contributions to cortisol response simply reflect magnification of standing genetic contributions to baseline variation in cortisol, or whether there are novel contributions of genetic factors not evident prior to stressor onset.…”
mentioning
confidence: 99%